2017
DOI: 10.1167/iovs.17-22895
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Aberrations in Former Preterm Infants: Results From The Wiesbaden Prematurity Study

Abstract: This study demonstrated that specific corneal aberrations were associated with extreme prematurity rather than with ROP occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 28 publications
(46 reference statements)
2
20
1
1
Order By: Relevance
“…Recent reports indicate that these alterations persist throughout life, as results from the Gutenberg Health Study showed that low birth weight (<2500 g) was associated with a steeper corneal radius, smaller corneal diameter [ 6 ], and altered posterior pole [ 28 , 29 , 30 , 31 ]. Furthermore, other studies reported a less regular corneal surface in subjects born preterm with low birth weight, as indicated by increased corneal aberrations in childhood and adulthood [ 9 , 10 ]. The present results indicate that prematurity affects not only ocular geometry but also other ocular surface properties such as tear film quantity and stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports indicate that these alterations persist throughout life, as results from the Gutenberg Health Study showed that low birth weight (<2500 g) was associated with a steeper corneal radius, smaller corneal diameter [ 6 ], and altered posterior pole [ 28 , 29 , 30 , 31 ]. Furthermore, other studies reported a less regular corneal surface in subjects born preterm with low birth weight, as indicated by increased corneal aberrations in childhood and adulthood [ 9 , 10 ]. The present results indicate that prematurity affects not only ocular geometry but also other ocular surface properties such as tear film quantity and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports observed that ROP is an additional parameter affecting corneal shape in children [ 1 ]. Additionally, the corneal surface is less regular as indicated by increased corneal aberrations measured in preterm children [ 9 ] and adults [ 10 ]. This is of particular importance because every year about 15 million newborns are born preterm globally and the prevalence of ROP has still been increasing for several decades worldwide [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CCT is negatively associated with body height [46] and positively associated with body weight in men and with body mass index in all subjects [40]. These parameters are known to be-at least partially-influenced by LBW and LBW may to some extent explain those associations with altered corneal thickness [5,7,9] and ocular geometry [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…[3] The major risk factors include extremely preterm delivery, high pO 2 levels during mechanical ventilation, and fluctuations in pO 2 [4]. It has been demonstrated that prematurity and postnatal ROP occurrence are associated with decreased visual acuity [5][6][7][8][9][10][11][12], higher frequency of refractive error [13][14][15][16], strabismus [17][18][19][20][21], and altered ocular geometry in childhood and adolescence [13,[22][23][24][25][26], however, the long-term effects of ROP and extreme prematurity on visual acuity and prevalence of amblyopia in adulthood are less well known. This is of relevance because over 15 million infants are born prematurely annually, thus reduced visual acuity in those subjects is a public health issue and economic burden [27].…”
Section: Introductionmentioning
confidence: 99%